Locus of Control Mediates Financial Attitudes, Knowledge, and Income effects on Millenial Financial Management Behavior in DKI Jakarta - Margareta Turnip; Herry Krisnandi (University of Merdeka Malang, 2023)
The millennial generation is capable of working and is already making money. However, a person's capacity for managing money is crucial, and this is connected to their finance knowledge. In this study, we investigate the effects of financial attitude, financial knowledge, and financial conduct on financial management behavior and locus of control, as well as the role of locus of control in mediating these associations. The study's sample included the following 220 millennials between the ages of 25 and 40 who were employed in the DKI Jakarta Province made up the sample for this study. The results of this study demonstrate that financial management behavior is highly influenced by financial attitude, financial knowledge, and income. Additionally, there is no obvious connection between locus of control and financial management practices. This study also discovered that income, financial knowledge, and financial attitude all significantly affect locus of control, but that locus of control is unable to mitigate the effects of these factors on financial management behavior.